Analisis Voltage Flicker Akibat Starting Motor Induksi Tiga Fasa di Rumah Pompa Karah Surabaya - Reza Sarwo Widagdo; Puji Slamet; Imam Suri Tauladan; Lutfi Agung Swarga; Bima Gilang Pratama; Izzah Aula Wardah (Politeknik Caltex Riau, 2026)
This study aims to analyze the causes of voltage flicker during the starting process of a three-phase induction motor at the Karah Pump House in Surabaya. The use of high power induction motors is essential for supporting flood control systems; however, conventional starting methods such as Direct On Line (DOL) and Star-Delta can generate high inrush currents that negatively affect power quality. The research evaluates starting current characteristics, distribution system impedance, and the resulting voltage flicker based on IEC standards. The analysis shows that the DOL method produces greater voltage drop and voltage flicker compared to the Star Delta method. Although the Star-Delta method is able to reduce voltage disturbances, both methods still have the potential to exceed standard flicker limits if the distribution system is not equipped with adequate mitigation devices. Therefore, proper starting current control is an important factor in maintaining power quality and ensuring the stability of the pump house distribution system.